2010
DOI: 10.1364/ol.35.001184
|View full text |Cite
|
Sign up to set email alerts
|

Timing-jitter, optical, and mode-beating linewidths analysis on subpicosecond optical pulses generated by a quantum-dash passively mode-locked semiconductor laser

Abstract: Timing-jitter measurements in optically generated subpicosecond pulses by a quantum-dash passively mode-locked semiconductor laser as a function of the bias current are reported. All the measurements are retrieved from a second-harmonic-generation frequency-resolved optical gating system. A decreasing trend in the pulse width and the associated timing jitter is found with the bias current. Additionally, the optical and mode-beating linewidths are analyzed in terms of both the mode wavelength and the bias curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 4 publications
1
18
1
Order By: Relevance
“…Furthermore, as depicted in Fig. 42(a), mode beating linewidth of 10 to 25 kHz was measured regardless of the bias current value and the timing jitter varied from 350 fs to 150 fs with peak power varying from 40 mW to 140 mW [300,301]. The influence of the bias current and the filter bandwidth on the pulses were also performed which revealed decrease in the pulse width either by increasing filter bandwidth or the bias current.…”
Section: Self-pulsationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as depicted in Fig. 42(a), mode beating linewidth of 10 to 25 kHz was measured regardless of the bias current value and the timing jitter varied from 350 fs to 150 fs with peak power varying from 40 mW to 140 mW [300,301]. The influence of the bias current and the filter bandwidth on the pulses were also performed which revealed decrease in the pulse width either by increasing filter bandwidth or the bias current.…”
Section: Self-pulsationmentioning
confidence: 99%
“…On the other hand, a 170 µm 6 stacks Qdash mode-locked laser exhibited 870 fs pulses at 245 GHz with 100 mW peak power and 7 dB extinction ratio. [245,301,304] Instead of the typical stepped-heterodyne technique for pulse characterization, Calo et al [305] employed the second-harmonic generation frequency resolved optical gating (SHG-FROG) technique for the investigation of high gain ~ 50 cm -1 , 1.56 µm, 9-stack InAs/InGaAsP dash-in-barrier laser. The 890 µm long device exhibited a repetition frequency of ~48 GHz under CW operation.…”
Section: Self-pulsationmentioning
confidence: 99%
“…It features more than 40 longitudinal modes with 0.31 nm inter-modal separation, resulting in a 3 dB optical bandwidth of 12 nm centered at 1526 nm [9], [10]. In free-running conditions, the QDash PMLL exhibits optical pulses featuring a width of 720 ps and a timing jitter of 150 s after a passive compression scheme [15]. A further detailed investigation of the dispersion compensation in this type of lasers to achieve the generation of picosecond pulses has been recently discussed in [16], [18].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…In terms of the timing jitter, Latkowski et al [82] utilized a 450-m long single mode dispersion-compensated fiber and demonstrated 720-fs wide pulses via a 39.8 GHz QD-MLL. Moreover, independently of the biasing current, a beating linewidth of 10e25 kHz was obtained with a timing jitter that varied from 350 to 150 fs while the peak power varied from 40 to 140 mW [83,84], as shown in Fig. 5.9A.…”
Section: Inas/inp Qdash Mode-locked Lasersmentioning
confidence: 99%